A PETROLOGIC AND ISOTOPIC STUDY OF WINONAITES: EVIDENCE FOR EARLY PARTIAL MELTING, BRECCIATION, AND METAMORPHISM - A PETROLOGIC-OXYGEN ISOTOPIC STUDY (ABSTR.) - Benedix G.K.; McCoy T.J.; Keil K.; Bogard D.D.; Garrison D.H. (My University, 1998)
We have conducted detailed petrologic, chemical, and isotopic studies of winonaites to ascertain the genesis of this group of meteorites. Winonaites have reduced mineral compositions and mineralogy, and oxygen isotopic compositions distinct from primitive achondrite groups other than silicate inclusions in IAB and IIICD irons. However, winonaites differ from IAB and IIICD irons in that they lack the metallic matrices of the latter and consist mostly of silicates. On the basis of these criteria, Winona, Mount Morris (Wisconsin), Tierra Blanca, Pontlyfni, Y-74025, Y-75300, Y-8005, and QUE 94535 are winonaites and Y-75305 and Y-75261 may be winonaites. Winonaites are fine- to medium-grained, mostly equigranular rocks. Pontlyfni and Mount Morris (Wisconsin) contain what appear to be relict chondrules. Several winonaites contain mm-sized areas that differ substantially in grain size and/or silicate mineralogy from the surrounding matrix. Fe,Ni-FeS veins are common in many winonaites. Mineral compositions are intermediate between E and H chondrites, and reduced sulfides are observed in low-FeO winonaites. Bulk major element compositions are roughly chondritic, although REE elements are fractionated. The 39Ar-40Ar ages of three winonaites range from =<4.40 Ga (Mount Morris, Wisconsin) to 4.54 Ga (Pontlyfni). Cosmic-ray exposure ages are ~20-80 Ma. Trapped noble gases in these winonaites resemble those in enstatite chondrites. We suggest that the winonaites formed from a chondritic precursor material unlike that of known chondrites in mineral and oxygen isotopic compositions, and this material may have been heterogeneous in composition. Extensive heating caused metamorphism and partial melting of both Fe,Ni-FeS and silicate material. Impact brecciation during cooling mixed lithologies with different thermal histories, and subsequent metamorphism produced recrystallization, grain growth, and reduction of mafic silicates. The 39Ar-40Ar ages indicate that cooling may have been more rapid than observed in IAB irons, although later resetting may have occurred.